Identification and experimental validation of circular RNA-associated ceRNA networks in intrauterine adhesion - Chang, Yajie; Xiang, Rui; Guo, Qi; Li, Jing; Li, Xiaolan; Zeng, Zhi; Peng, Jintao; Liang, Xiaoyan (Frontiers in Genetics, 2025)
Intrauterine adhesion (IUA) is characterized by endometrial fibrosis, posing significant risks to women’s reproductive health and fertility. This study aimed to uncover a circRNA-associated ceRNA regulatory network relevant to intrauterine adhesion (IUA), thereby contributing to the understanding of its molecular pathogenesis. The expression data of circRNAs and mRNAs in endometrial tissues of IUA and normal controls were analyzed by RNA sequencing, and microRNAs (miRNAs) expression data was downloaded from GSE165321. Our analysis identified 44 differentially expressed (DE) circRNAs, 41 DEmiRNAs, and 640 DEmRNAs. A comprehensive circRNA-miRNA-mRNA network was constructed using Cytoscape. DEmRNAs were mainly enriched in extracellular matrix structural components, collagen fiber complexes. KEGG pathway analysis further implicated the NF-κB signaling pathway, apoptosis, and Notch signaling in IUA development. A protein-protein interaction network for ceRNA-associated mRNAs was developed through the STRING database, highlighting potential hub genes. To validate these transcriptomic findings, RT-qPCR confirmed significant upregulation of the two leading hub circRNAs, hsa_circ_0000439 and hsa_circ_0000994, in IUA samples compared to normal controls, with results showing consistency with RNA sequencing data (p < 0.05). Functional experiments demonstrated that silencing hsa_circ_0000994 with siRNA in vitro significantly decreased the expression levels of fibrosis markers α-SMA and COL1A1 in human endometrial stromal cells treated with TGF-β1. In conclusion, this study presents an in-depth transcriptomic analysis of the aberrantly expressed circRNAs, miRNAs, and mRNAs in endometrial tissues from patients with IUA, culminating in the establishment of a novel circRNA-miRNA-mRNA regulatory network. Hsa_circ_0000994 is likely to play a pivotal role in modulating fibrosis associated with IUA, and represents a promising candidate for targeted therapeutic approaches.